(untitled) (Third Sector Social Economic Review, 2023)
Until 1960’s, the researches carried out in accounting field are determined completely by the neo-classical assumptions about rational decision making of capital markets and actors. Although a large part of the work still depends on these assumptions, it is clear that a research field that has questioned these assumptions for the last 30-40 years is evolving. The developments have a close relationship with accounting and this contributes to the change and development of traditional accounting. The emergence of behavioral accounting (BA), which examines the behavior of financial information producers or users in the face of an accounting event, is a result of this change. BA practices in businesses are gathered in four groups; BA and motivation, BA and ethics, BA and performance evaluation and budgeting, and BA and auditing. The fourth, behavioral examination of auditing, represents the subject of this paper. The purpose of this study is (1) to discuss the situation of BA from auditing dimension by considering the factors that may affect the decision-making behaviors of auditors, (2) to explain the heuristics and cognitive biases that are selected from behavioral approach and (3) to present results by associating this literature with auditing. Study also offers suggestions for future behavioral studies in the dimension of auditing and decision-making aspects.